(untitled) (Olhar de Professor, 2023)
This article is organized in two moments. Firstly, it shows a short Pedagogy course record in Brazil, by having as time frame his appearance in 1939 since the Resolution n. 02/2019 (BNC-Formação). The historical-legal points image about the Pedagogy course will follow in a methodological descriptive-analitic way perpassing by legal pieces, as well as by the creation of moviments, associations and constructed entities over the framed period, in the dialogue with authors with research tradition in the teachers field training, like: Cruz, Gatti, Libâneo, Saviani and Scheibe. Then, it presents elements that unveil the regress and the own crumbling of the Pedagogy course from the express assumptions by the Resolution n. 02.2019. Their objective is reflect in the historical-legal dimention on the curricular projects of the teachers formation courses, with an emphasis in the Pedagogy course, this research study object.